Lack of correlation between water hardness and salivary calculi in England - J.A. Sherman, M. McGurk (Blackwell Synergy, 2000)
Calculous disease is a relatively common cause of salivary gland infection in adults, and to a lesser extent in children. In a review of 1200 cases by Rauch, 83% of stones were located in the submandibular system, 10% in the parotid, and 7% in the sublingual glands.